2017
DOI: 10.1007/s11695-017-2834-z
|View full text |Cite
|
Sign up to set email alerts
|

The Socio-economic Impact of Bariatric Surgery

Abstract: There are no cost savings of bariatric surgery in the short run. Further real-world evidence over a longer period of time is needed to examine whether the higher health care costs will eventually be counterbalanced, making bariatric surgery a profitable intervention in a socio-economic perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 62 publications
1
19
1
2
Order By: Relevance
“…After removing duplicate papers 1096 studies remained for title and abstract screening, with 63 studies included for full‐text review. Of these, 24 partial and full health economic evaluation studies were included in the updated systematic review . These studies were also assessed against the eligibility criteria for quantitative meta‐analyses together with the n = 77 eligible health economic evaluations from our previous systematic review (low part of Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After removing duplicate papers 1096 studies remained for title and abstract screening, with 63 studies included for full‐text review. Of these, 24 partial and full health economic evaluation studies were included in the updated systematic review . These studies were also assessed against the eligibility criteria for quantitative meta‐analyses together with the n = 77 eligible health economic evaluations from our previous systematic review (low part of Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, of the remaining 61 studies included in our meta‐analyses, 34 (56%) and 27 (44%) were based on partial and full health economic evaluations, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This might also be the case in other countries or healthcare systems where newer and more expensive drugs are employed. It is noteworthy that Kelles et al Moreover, as reported by Larsen et al (18), results on the ability of bariatric surgery to generate healthcare savings are inconsistent. In their study, the authors investigated the impact of bariatric surgery on healthcare costs, social transfer payments, and income in a surgical vs. nonsurgical group in 7 years (3 years preoperatively, year of surgery, and 3 years postoperative) in Denmark.…”
Section: ' Discussionmentioning
confidence: 98%